Proximal Smoothness and the Exterior Sphere Condition - Nour, C. (2009)
Proximal smoothness and the exterior sphere condition are compared. It is shown via examples that these two properties are not necessarily equivalent, and geometric conditions are provided under which the equivalence holds.